Biomarcadores e análises microbiológicas para detecção de potenciais riscos à saúde humana utilizando Sciades herzbergii (Siluriformes: Ariidae) da costa amazônica - MACEDO, Gustavo Henrique Rodrigues Vale de (2024)
Biomonitoring studies in industrial and port areas are essential to initiate interventions that aim to minimize economic, environmental and social damage. In this context, this study aimed to measure physicochemical parameters of water, analyze hepatic biomarkers of oxidative stress, as well as isolate and identify pathogenic Gram-negative bacteria in the skin, intestines and muscles and observe histological changes in the gill and liver of Sciades herzbergii, a species of estuarine catfish caught near a port complex on the Brazilian Amazon coast. Physicochemical parameters of the water, biometric indices of the fish, enzymatic parameters such as superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), glutathione S-transferase (GST) and lipoperoxidation reactions (LPO), were analyzed in the periods rainy (May) and drought (November) of 2021 and 2022 in two regions: Porto Grande (PG, area potentially impacted by port activities) and Ilha dos Caranguejos (IC, conservation area). The identification and quantification of bacteria from the coliform group was carried out using COLItest® (LKP, São Paulo, Brazil), with the identification and phenotypic investigation of antimicrobial resistance using the Vitek® automated system. Gill and liver samples were subjected to the usual histological technique. Lower levels of dissolved oxygen and higher concentrations of trace metals and polycyclic aromatic hydrocarbons were detected in PG sediments. PG fish showed delayed development, increased enzymatic activities and increased lipid peroxidation. The analysis of the main components showed a greater expression of oxidative stress during the rainy season, especially for the year 2022. The results obtained also indicated the presence of pathogenic strains of Klebsiella pneumoniae and Escherichia coli (thermotolerant coliform), the latter having presented phenotypes resistance to norfloxacin and gentamicin. More significant gill and liver damage was identified in catfish from PG, such as lamellar narrowing and fusion, necrosis, infiltration of inflammatory cells, hemorrhage and cells in differentiation. Thus, chemical contamination of estuaries directly influences the expression of oxidative stress enzymes in S. herzbergii, harming fish health, and histological changes in exposure organs may also have potentially been influenced by infection with pathogenic Gram-negative bacteria, which poses significant risks to human health.